A Critical Analysis of the Liberal International Order - Sajadi, Dana M.D. (Mağallaẗ ğāmiʻaẗ Ğīhān- Arbīl li-l-ʻulūm al-insāniyyaẗ wa-al-iğtimāʻiyyaẗ, 2025)
People generally understand that the liberal international system came about after World War II and reached its peak around 1990. As the Soviet Union or what is called the Eastern campus fell apart, it paved the way for the US-led Western nations to take over and become the main driving force in international politics, changing the dynamics of the international system, and shifting the way things work on the global stage, moving from a bipolar into a unipolar system, making the United States the sole power. In addition, spreading the political and economic principles of liberal international order where the foundation of the system is shaped by these twofundamental pathways. However, over the last few years, the United States has encountered certain difficulties in upholding its dominance and advocating for its established system. The economic path might be manageable, but the political approach of democratic peace seems to be creating more divisions around the world. Difficulties, such as the emergence of influential regional players such as China and Russia, as well as the war in Ukraine, which is not just a regional conflict but a trial for the position of the existing global system. Therefore, the paper sheds light on the challenges confronting the current international order and the role of American leadership by analyzing historical developments, geopolitical dynamics, and ideological shifts, and the paper aims to illuminate the intricacies of this transition.